Influence of terminal drought stress on root and biochemical parameters in groundnut (Arachis hypogaea L.): Influence of terminal drought stress on root and biochemical parameters in groundnut (Arachis hypogaea L.) - CHANDRASHEKHARA G; HASANALI NADAF; B N HARISH BABU (Journal of Oilseeds Research, 2020)
A study on influence of terminal drought stress on biochemical and root responses in forty genotypes was conducted. Due to drought stress imposition at 90 days after sowing (DAS), phenolic content of seeds and root length of treated plants were decreased, whereas, oil content, phenolic content of leaves, protein content of both leaves and seeds and root to shoot ratio were increased compared to normal plants. This indicates that physio- biochemical and root responses of groundnut are influenced by soil moisture during growth stages and it also affects duration of crop growth period as all these are inter-related with one another.